2020
DOI: 10.1186/s12936-020-03319-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Plasmodium vivax antifolate resistance markers in Afghanistan between 2007 and 2017

Abstract: Background: Plasmodium vivax is the predominant Plasmodium species in Afghanistan. National guidelines recommend the combination of chloroquine and primaquine (CQ-PQ) for radical treatment of P. vivax malaria. Artesunate in combination with the antifolates sulfadoxine-pyrimethamine (SP) has been first-line treatment for uncomplicated falciparum malaria until 2016. Although SP has been the recommended treatment for falciparum and not vivax malaria, exposure of the P. vivax parasite population to SP might still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Quadruple 57L/58R/61M/117T, triple 57L/58R/117 and double pvdhfr (57L/117N) mutant haplotypes have been associated with in vitro drug resistance 16 . This study found pvdhfr double mutant S58R + S117N in 25% of clinical isolates reported from neighboring countries like India, Afghanistan and Iran [27][28][29] .…”
Section: Discussionmentioning
confidence: 52%
“…Quadruple 57L/58R/61M/117T, triple 57L/58R/117 and double pvdhfr (57L/117N) mutant haplotypes have been associated with in vitro drug resistance 16 . This study found pvdhfr double mutant S58R + S117N in 25% of clinical isolates reported from neighboring countries like India, Afghanistan and Iran [27][28][29] .…”
Section: Discussionmentioning
confidence: 52%
“…Quadruple 57L/58R/61M/117T, triple 57L/58R/117 and double pvdhfr (57L/117N) mutant haplotypes have been associated with in vitro drug resistance 16 . This study found pvdhfr double mutant S58R + S117N in 25% of clinical isolates reported from neighboring countries like India, Afghanistan and Iran [27][28][29] .…”
Section: Discussionmentioning
confidence: 52%